2011
DOI: 10.5049/ebp.2011.9.2.50
|View full text |Cite
|
Sign up to set email alerts
|

V2 Receptor Antagonist; Tolvaptan

Abstract: Hyponatremia is the most common electrolyte disorder in hospitalized patients. Many studies documented that it was related to increased morbidity and mortality in patients with congestive heart failure, liver cirrhosis, and neurologic diseases. Although knowledge of hyponatremia has been cumulated, the optimal management of hyponatremia remains incompletely established in clinical practice because of the diversity of underlying disease states, and its multiple causes with differing pathophysiologic mechanisms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 17 publications
0
15
0
3
Order By: Relevance
“…[16][17][18] In addition to these indications, add-on therapy of tolvaptan to conventional diuretics is expected to be useful for the treatment of hepatic oedema, since tolvaptan induces the secretion of free water without sodium excretion (aquaresis). 19 In a pharmacokinetics/pharmacodynamics study, tolvaptan was shown to decrease body weight and ascites volume, and increase urine output, in a dose-dependent manner. 20 Additionally, a dose-finding study investigating the effect of a 7-day treatment with tolvaptan 7.5, 15, and 30 mg/day in hepatic oedema, determined that the optimal dose of tolvaptan was 7.5 mg/day, based on reductions in body weight and abdominal circumference.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] In addition to these indications, add-on therapy of tolvaptan to conventional diuretics is expected to be useful for the treatment of hepatic oedema, since tolvaptan induces the secretion of free water without sodium excretion (aquaresis). 19 In a pharmacokinetics/pharmacodynamics study, tolvaptan was shown to decrease body weight and ascites volume, and increase urine output, in a dose-dependent manner. 20 Additionally, a dose-finding study investigating the effect of a 7-day treatment with tolvaptan 7.5, 15, and 30 mg/day in hepatic oedema, determined that the optimal dose of tolvaptan was 7.5 mg/day, based on reductions in body weight and abdominal circumference.…”
Section: Introductionmentioning
confidence: 99%
“…d The chest X-ray at discharge demonstrated improved cardiomegaly with no sign of congestion Tolvaptan is also used postoperatively for heart surgery patients. The add-on treatment of tolvaptan to conventional diuretics is anticipated to be useful for hepatic edema because tolvaptan increases excess fluid excretion and improves blood sodium levels without causing sodium excretion [4]. The effectiveness of tolvaptan for hepatic edema has been reported [5].…”
Section: Discussionmentioning
confidence: 99%
“…Los vaptanes constituyen una familia con base fisiopatológica sólida y se han mostrado eficaces y seguros, y vienen a ocupar un hueco terapéutico, principalmente en el manejo de la hiponatremia euvolémica, donde las otras alternativas terapéuticas, escasas, se han demostrado insuficientes [90][91][92][93][94][95][96][97][98][99][100] . En EE.…”
Section: Vaptanes En El Tratamiento De La Hiponatremiaunclassified
“…Esta posibilidad no parece de importancia en el uso de estos fármacos en breves períodos de tiempo; sin embargo, el empleo a largo plazo no se conoce y puede requerir una monitorización estrecha cuando se emplean otros fármacos que se metabolizan por esa vía 96,99,100 . Esta posibilidad no parece de importancia en el uso de estos fármacos en breves períodos de tiempo; sin embargo, el empleo a largo plazo no se conoce y puede requerir una monitorización estrecha cuando se emplean otros fármacos que se metabolizan por esa vía 96,99,100 .…”
Section: Interacciones Medicamentosasunclassified
See 1 more Smart Citation